Economic Impact of Inflammatory Bowel Disease in Alberta - B.R. Pinchbeck; J. Kirdeikis; A.B.R. Thomson (Canadian Journal of Gastroenterology)
This paper attempts to estimate the cost of inflammatory bowel disease (IBO) to the health care system of Alberta. In the 1015 patients responding to a questionnaire, two types of direct costs were compared to provincial averages; physicians' fees and hospital costs. Costs were calculated using the Alberta Health Care Insurance Plan prescribed billing races. The 15-to 24-year-old age group exhibited the highest annual physician fees. This was probably due to the high incidence rate of IBD in this group. The mean cost per patient-year for Crohn's disease was estimated to be $4400 and the mean cost for ulcerative colitis was estimated to be $3020; this did not include outpatient laboratory or radiological investigations, and as such represents an underestimation of the total costs to the health care system. However, only a small minority of the patients were using a large majority of the resources: for example, for both Crohn's and ulcerative colitis, 7% of the patients accounted for 69% of hospital days. The average hospital and physician associated costs declined markedly with duration of the disease. It is estimated that the future cost of IBO to the provincial health care system (the percentage of the provincial health care budget used to diagnose and treat IBO) will double from 1985 to 2000. This underscores the need for continued and expanded research into the cause and treatment of IBO, and the importance of maintaining a health care system which can respond to the needs of these patients.